A aprendizagem de competências evidenciadas pelos alunos do curso de Tecnologia em Comércio Exterior - Pereira, Marcelo Almeida de Camargo (2014)
This dissertation, inserted in the research line of Teacher Training, Theories and Educational Practice in the Post-Majoring Program of Master in Education at Centro Universitário La Salle (UNILASALLE), aimed to analyze how a group of undergraduate students of the technology course of International Business comprehend the learning of competencies for their professional training. As review of literature, a study about competencies and abilities was made, based both on Perrenoud (1999, 2000) and Zabala and Arnau (2010), that explain about the different knowledge mobilized on the competencies, as well as the teaching knowledge involved on them, the latter based on Tardif (2004). The concepts of competencies and abilities were also studied under the Business point of view, based on Rocha Neto (2003), Fleury e Fleury (2004) and Zarifian (2003), where the similarities and differences of the epistemological concepts among the Education and Business views were pointed. An exploratory study was also made about the technology graduation in Brazil, the context of Brazilian international trade and the expected competencies of the international business professional. The methodology used was qualitative and the data were collected by focus groups. For the analysis of data, the Discursive Text Analysis technique, based on Moraes (2003) was used, where a metatext, result of a process of deconstruction and categorization was elaborated. The results presented demonstrate that learning competencies is seen as a process with multiple interactions and relations with the other participants in the educational process, where the will of obtaining a degree for insertion in the labor market widely depends on one’s attitudes to their commitment on an active learning.